RESEARCH ON CUTTING PROPAGATION OF GARDENIA JASMINOIDES - Vu Tho, Hoang; Bich Ngoc, Hoang (Journal of Forestry Science and Technology, 2019)
The article introduces the results of the research on clonal propagation by cuttings method of Gardenia jasminoides, using type hormones and different concentrations obtained results with rooting ratio; while average roots per cuttings; average root length per cuttings and rooting index; total number of shoots; average shoots per cuttings; and average shoots length per cuttings are very different, when using Indole-3-butyric acid (IBA) achieved higher results. The usage of IBA at concentration of 1500 ppm obtained the results with the highest rooting rate (83.4%), the average number of roots per cuttings was 29.9 roots, average root length per cuttings was 3.3 cm, and the rooting index achieved was 97.9. Using a-Naphthalene acetic acid (NAA) at concentrations of 250 and 500 ppm (CT5 and CT6) obtained results with the highest rooting ratio, and total sproutings shooting (80.0% and 126 shoots respectively), while at higher concentration (1500 ppm) obtatined results reaching the highest value with the average number of roots per cuttings, and rooting index are 16.9 and 59.7 respectively. Using IBA (CT2) and NAA (CT6) at concentrations of 500 ppm in order to propagate Gardenia jasminoides by cuttings was able to promote sprouting shooting with highest values achieved were 129 and 126 respectively. The results of this study are the basis for further studies to get the success of the clonal propagation of G. jasminoides for planting and development.